The impact of large fires in boreal drained peatlands in western Finland: Ecohydrological drivers and carbon and nitrogen loss - Turunen, Jukka; Rehell, Sakari; Sarkkola, Sakari; Vasander, Harri (Elsevier, 2025)
Climate change, characterized by more frequent drought periods along with anthropogenic activities, may increase the occurrence and severity of peatland wildfires in the boreal region. This study examines the impact of two large-scale peatland fires in 2020 and 2021 on carbon (C) and nitrogen (N) dynamics and losses in western Finland. The first site (Muhos, burned peatland area 217 ha) included both drained peatlands and pristine undrained mires, while the second (Susineva, burned peatland area 130 ha) was entirely drained for forestry. Our results reveal the significant impact of high-intensity fires on C and N dynamics and storage in drained peatlands, and in undrained mires with variable water regimes. In well-drained peatlands used for forestry, the average C and N losses during the fire were approximately 5.5 kg C m−2 and 123 g N m−2. This estimated C loss exceeds the typical range reported for fire-events in undrained boreal mires. In contrast, the C loss in the undrained or poorly drained area fell within the range observed for undrained mires. The measured fire severity was influenced by drainage intensity and the types of vegetation communities. In undrained mires, the upper aerobic layer, with stable water regime, tends to burn only superficially or may even remain unburnt. However, in shallow mires with a variable water regime, where the surface peat dries extensively during drought periods, the C loss caused by fire was comparable to drained peatlands. Our findings underscore the importance of understanding the ecosystem services provided by peatlands, particularly considering management-related drivers such as drainage and fires. These factors can severely impact the peatland C balance and overall vulnerability, including reduced fire resilience.
Keywords: fire ecology; carbon; nitrogen; emissions; boreal region; Finland; peatland fire